CONTINUOUS VERSUS INTERRUPTED SUTURES FOR REPAIR OF EPISIOTOMY OR 2ND DEGREE PERINEAL TEARS - Aslm, Rakhshanda; Khan, Shazia Amir; amir, Zain ul; Khan, Fouzia Amir Amir (Journal of Ayub Medical College Abbottabad, 2015)
Background: Performing an episiotomy is generally reserved for complicated childbirths, in cases of foetal distress, or when tearing of tissues with serious consequences are foreseen. In addition to the extent of the trauma, the surgical skill, repair after childbirth can have an important effect on the magnitude and degree of morbidity experienced by women after repair. The best technique for this repair would be that which produces less pain in the short and long term. The study was done with an objective to compare the frequency and severity of pain (slight/severe) by using interrupted and continuous methods for repair of episiotomy or second degree perineal tears. Methods: It is a randomized control trial. This study was carried out in a Gynaecology and Obstetrics department of Benazir Bhutto Hospital Rawalpindi which is a tertiary care hospital. The duration of study was six months. One hundred & thirty-eight primigravidas (69 in each group) were included in the study. Results: Majority of the patients in both groups belonged to 20-25 years age group, i.e., 48.53% (n=33) in group-A and 50% (n=34) in group-B, mean and sd, was 27.69±3.21 in group -A and 28.16±3.89 in group-B, gestation age of the patients in group-A 77.94% (n=53) and 83.82% (n=57) in group-B between 37-40 weeks of gestation. Complication of pain and its severity in both groups at 24 hours and 10th day were compared which showed no significant difference at any severity (i.e., no pain, mild moderate/severe). Conclusion: There is no significant difference in frequency and severity of pain (slight/severe) in using interrupted and continuous methods for repair of second degree perineal tears or episiotomy